Chronic Obstructive Pulmonary Disease and Vascular Disease Delay Timeliness of Early Stage Lung Cancer Resectional Surgery. (21st March 2013) - Seda, Gilbert; Stafford, Christopher C.; Parrish, John S.; Praske, Steven P.; Daheshia, Massoud
Abstract Introduction: Lung cancer remains the leading cause of cancer death in the United States and worldwide. Timeliness to diagnosis and referral for resectional surgey is key to successful management for early stage disease. Methods: We investigated the contribution of medical co-morbidities in the timeliness to resectional surgery for non-small cell lung cancer (NSCLC). A retrospective record review of NSCLC surgery cases at Naval Medical Center San Diego (NMCSD) from 2004 to 2009 from the tumor registry was conducted. Results: More than 75% of NSCLC patients exhibited at least one co-morbidity. Of the 84 patients, 26% of patients had diabetes, patients with different vascular co-morbidities accounted for 39%, whereas 33% of subjects had COPD. Patients with sleep apnea or liver disease each accounted for 6%. Vascular disease co-morbidity and COPD in NSCLC patients significantly delayed time from initial cardiothoracic surgery evaluation to thoracotomy (p = 0.01–0.02 and p < 0.05 respectively). Conclusion: Although significances of different co-morbities in the development NSCLC cannot be extrapolated, theses data show that COPD and vascular diseases are significant risk factors that delay surgical treatment of early stage lung cancer.